How to build sustainable and profitable customer loyalty/ Relationship through the help of CRM systems to improve Business Performance and profitability of the company? - Pandey, Nimesh (2011)
Executive Summary Today the business world is rapidly changing and in a middle of vast transition. From brand and product centric to service centric, the companies are striving to become much more customer centric. As a result customer has become the central of all the operations of the organization. This actually points forward to the concept of relationship marketing where companies do not look at the customer from single transaction point of view, but want to set up a long term relationship with their customers. Relationship Marketing has further engaged into customer relationship management commonly known as CRM. Customer relationship management helps the companies to handle the vast amount of data available to them about the customer, so that they know customer better and can tailor their offerings with respect to individual customer.